2023
DOI: 10.3390/ijerph20105825
|View full text |Cite
|
Sign up to set email alerts
|

Has the COVID-19 Pandemic Affected Cyberbullying and Cybervictimization Prevalence among Children and Adolescents? A Systematic Review

Abstract: In light of the alarming results emerging from some studies and reports on the significant increase in aggressive online behaviors among children and adolescents during the COVID-19 pandemic, the current research aimed at providing a more detailed evaluation of the investigations focusing on the cyberbullying prevalence rates published between 2020 and 2023. To this purpose, systematic searches were conducted on four databases (Web of Science, APA PsycInfo, Scopus and Google Scholar), and following PRISMA guid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 115 publications
0
2
0
Order By: Relevance
“…Additionally, Axell [47] revealed that young females aged 16-24 are likelier to experience intimate partner violence compared to females over 25 years, with one in five reporting various forms of victimisation by their partner or ex-partner. However, in the context of cyberbullying involving children and adolescents during the COVID-19 pandemic, Sorrentino et al [48] conducted a systematic review and found an increase in the prevalence of cyberbullying in several Asian countries and Australia, while Western countries experienced a decline. Interestingly, our study indicated a higher proportion of adolescents reporting a decrease rather than an increase of victimisation, with significantly more males reporting a decreased frequency compared to females.…”
Section: The Frequency Of Victimisation Before and During The Covid-1...mentioning
confidence: 99%
“…Additionally, Axell [47] revealed that young females aged 16-24 are likelier to experience intimate partner violence compared to females over 25 years, with one in five reporting various forms of victimisation by their partner or ex-partner. However, in the context of cyberbullying involving children and adolescents during the COVID-19 pandemic, Sorrentino et al [48] conducted a systematic review and found an increase in the prevalence of cyberbullying in several Asian countries and Australia, while Western countries experienced a decline. Interestingly, our study indicated a higher proportion of adolescents reporting a decrease rather than an increase of victimisation, with significantly more males reporting a decreased frequency compared to females.…”
Section: The Frequency Of Victimisation Before and During The Covid-1...mentioning
confidence: 99%
“…Additionally, Axell [51] revealed that young women aged 16-24 are likelier to experience intimate partner violence compared to women over 25 years, with one in five reporting various forms of victimisation by their partner or ex-partner. However, in the context of cyberbullying involving children and adolescents during the COVID-19 pandemic, Sorrentino et al [52] conducted a systematic review and found an increase in the prevalence of cyberbullying in several Asian countries and Australia, while Western countries experienced a decline. Interestingly, our study indicated a higher proportion of adolescents reporting a decrease rather than an increase in victimisation, with significantly more men reporting a decreased frequency compared to women.…”
Section: Risk Behaviours Before and During The Covid-19 Pandemicmentioning
confidence: 99%
“…We collected data from an urban primary school using a convenience sampling method, which limited the representativeness of the findings. Demographic characteristics of the survey sample, economic development, geographical location, cultural backgrounds, and Internet penetration rates may contribute to different cyberbullying victimization rates [15]. In the future, longitudinal studies with larger samples should be conducted to better explore whether and how childhood experiences of cyberbullying affect mental health later.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…A study of urban secondary school students in Guangdong province, China, reported a cyberbullying victimization rate of 44.5% [13], while the rate in rural primary and secondary school students in Shandong province, China, was 11.4% [14]. Variations in research tools and instruments, demographic characteristics of the survey sample, economic development, geographical location, cultural backgrounds, and Internet penetration rates may contribute to different cyberbullying victimization rates [15]. Researchers found that cyberbullying can cause many psychological adaptation issues (e.g., anxiety and depression) [16].…”
Section: Introductionmentioning
confidence: 99%